The Dynamics of Chinese Culture in the Suryakencana Chinatown Area of Bogor in 1970-2016 - Ansyahdi, Hilma Ahda; Rustanama, Agus; Fadillah, Moh Ali (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine the the Dynamics of Chinese Culture in the Suryakencana Chinatown Area of Bogor In 1970–2016. The method used in this research is historical methods, which includes several stages, namely heuristics, criticism, interpretation, and historiography. The research results show that there is a creation of China's central economic and residential area (Chinatown) which ultimately creates a cultural adaptation process that occurs between ethnic Chinese and local Sundanese communities in Suryakencana Chinatown area, This can be seen in elements of art, religion and infrastructure such as, Cap Go Meh cultural festival, Tangsin Ritual, and Lawang Suryakencana. The conclusions of this research show that the process of cultural adaptation has the potential to occur due to several factors such as, there are similarities between traditional Chinese culture and traditional Sundanese culture, the historical background of the Chinese people who made their living as traders, The basic nature of Chinese people is very adaptable and Sundanese people are known to be friendly. Besides that, During the development, three processes of cultural adaptation occurred, namely substitution, syncretism and addition.